Protective effect of autophagy in neural ischemia and hypoxia: Negative regulation of the Wnt/β-catenin pathway - Shi, Zhen-Yu; Deng, Jie-Xin; Fu, Su; Wang, Lai; Wang, Qiang; Liu, Bin; Li, Yong-Qiang; Deng, Jin-Bo (International journal of molecular medicine, 2017)
Autophagy is a highly conserved process of self-digestion to promote cell survival in response to nutrient starvation and other metabolic stresses. However, whether ischemic-hypoxic (IH) injury-induced autophagy acts as a neuroprotective mechanism or leads to neuroinjury is a subject of debate. It is known that autophagy is regulated by signaling pathways, including the mammalian target of rapamycin pathway. However, in neural IH injury, whether other signaling pathways are involved in the regulation of autophagy remains to be fully elucidated. In the present study, using the autophagy agonist (rampycin), autophagy antagonist [3-methyl adenine (3-MA)] and lysosome antagonist (MHY1485), autophagy was intervened with at oxygen-glucose deprivation (OGD) 6 h, in order to elucidate the regulatory mechanisms of autophagy. Using immunocytochemistry and western blot analysis, the expression levels of stress-related proteins, such as hypoxia-inducible factor-1α (HIF-1α) (a key regulator in hypoxia) and cyclooxygenase 2 (COX2; inflammatory indicator), were analyzed. In addition, the upstream proteins (Wnt1 and Wnt3a), downstream proteins (Dvl2, β-catenin) and target proteins (C-myc and cyclin D) in the Wnt/β-catenin signaling pathway were examined by immunocytochemistry and western blot analysis. The present study revealed that autophagy was activated with the upregulation of autophagic flux in IH injury; it was demonstrated that autophagy had a protective role in IH injury. The Wnt/β-catenin pathway was involved in IH injury regulation, and the upstream proteins in the Wnt/β-catenin signaling pathway were upregulated, whereas downstream proteins were downregulated by the activity of autophagy accordingly.